Behavior and daily activity patterns of specialist and generalist predators of the hemlock woolly adelgid, Adelges tsugae - Flowers, Robbie W.; Salom, Scott M.; Kok, Loke T.; Mullins, Donald E. (My University, 2007)
The behavior and daily activity patterns of two specialist predators, Laricobius nigrinus Fender (Coleoptera: Derodontidae) and Sasajiscymnus tsugae, Sasaji and McClure (Coleoptera: Coccinellidae), and a generalist predator, Harmonia axyridis Pallas (Coleoptera: Coccinellidae), of hemlock woolly adelgid, Adelges tsugae (Hemiptera: Adelgidae), were examined using digital video recording in the laboratory. The two specialists are part of a biological control program for A. tsugae, and it is not known if competitive interactions with previously established generalist predators will negatively impact their effectiveness. The behavior and daily activity patterns of adult females of each species were documented in single- and paired-predator assays under simulated spring and summer conditions. Behavior varied qualitatively and quantitatively by species, and did not appear to be highly coordinated temporally or spatially. All species exhibited continuous activity patterns that were punctuated by longer periods of rest. Extensive and intensive searching behavior occurred in all species, with intensive searching being highly variable. Specialist predators appeared to be more selective of feeding and oviposition sites, and rested at more concealed locations than the generalist species. In spring conditions, L. nigrinus had greater activity and a more even behavior distribution than S. tsugae or H. axyridis, which were skewed towards resting. In summer, the latter two species showed increased activity at higher temperatures. Conspecifics significantly altered the time allocated to specific behaviors for L. nigrinus and H. axyridis, resulting in reduced predator effectiveness by reducing time and energy expenditure on activities that directly impact the adelgids. In contrast, S. tsugae conspecifics and all heterospecific combinations showed non-interference. The activity of each species varied with time of day; L. nigrinus was more active at night, while S. tsugae and H. axyridis were more active during the day. All predator groupings maintained a high degree of spatial separation relative to assay size. The use of multiple-predator species combinations that include the specialist predators, is recommended over single-species for biological control of A. tsugae, as temporal and spatial patterns were not highly coordinated. Low-density releases may reduce the potential negative effects of intraspecific competition.
This video accompanies a forthcoming article in the Journal of Insect Science.
Keywords: Laricobius nigrinus; Sasajiscymnus tsugae; Harmonia axyridis; predator competition; biological control